Vision of the students of the University of Tabuk on the culture of entrepreneurship - al-Dabbousi, Sami al-Akbar (Journal of Economic, Administrative and Legal Sciences, 2017)
This research aims at highlighting the entrepreneurship culture. The concepts of entrepreneurship and entrepreneurial culture were discussed in theoretical terms. The advantages, disadvantages and risks of entrepreneurship as well as the characteristics of entrepreneurs were also presented. The practical aspect of this research was to study the entrepreneurship culture among students of the University of Tabuk during the academic year 2016/2017. The results showed that the students of the University of Tabuk are looking for job security in the public sector rather than personal initiatives and self-employment. The study also revealed a strong relationship between the student environment and the idea of ​​the project to be completed. The research also revealed a concentration at the level of the Tabuk region in the projects to be completed. As we have noted through the results of the study there is a tendency to individual projects and fear of partnership. A number of recommendations were proposed to support and promote the culture of entrepreneurship, most notably the recommendation to develop the entrepreneurship program at the University of Tabuk and the inclusion of the entrepreneurship course as an obligatory course in all disciplines offered at all colleges of the University of Tabuk.
Keywords: entrepreneurship; entrepreneurial culture; entrepreneur